A monolithic metal-free electrocatalyst for oxygen evolution reaction and overall water splitting. Issue 11 (26th September 2016) - Balogun, Muhammad-Sadeeq; Qiu, Weitao; Yang, Hao; Fan, Wenjie; Huang, Yongchao; Fang, Pingping; Li, Gaoren; Ji, Hongbing; Tong, Yexiang
Abstract : Herein, a three-dimensional monolithic and metal-free N-doped porous carbon cloth electrocatalyst was fabricated. Abstract : Herein, a three-dimensional monolithic and metal-free N-doped porous carbon cloth electrocatalyst was fabricated. Owing to the increased surface area and N-doping, the self-supporting electrocatalyst could effectively catalyze the oxygen evolution reaction, and was also utilized as the anode for an alkaline electrolyzer for the first time with a considerably low overpotential.